Tight junction channel regulation by interclaudin interference - Nitesh Shashikanth; Marion M. France; Ruyue Xiao; Xenia Haest; Heather E. Rizzo; Jose Yeste; Johannes Reiner; Jerrold R. Turner (Nature Communications, 2022)
Tight junctions are formed by claudin proteins that can be classified as pore- or barrier-forming. Here, Shashikanth et al. report a third function, termed interclaudin interference, in which one claudin inhibits pore function of another claudin by disrupting its polymeric complexes.